Answer:
Equation 1 needs to be multiplied with + 2
Equation 2 needs to be multiplied with + 5.
Explanation:
Here, the given system of equation is given as:
Equation 1 : 6 x − 5 y = -4
Equation 2: 4 x + 2 y = 28
Here, in equation 1, the coefficient of y = - 5
Also, in the equation 2, the coefficient of y = + 2
Now, in order to eliminate the y coefficients,
Coefficient of y in 1 = - Coefficient of y in 2
Now, to make -5 and + 2 to eliminate each other,
Multiply -5 with 2, we get -5 x 2 = -10
And Multiply the coefficient + 2 with 5, we get +2 x 5 = + 10
The new coefficient of y is equation 1 = - 10 y
The new coefficient of y in equation 2 = + 10 y
They will cancel out each other, when both equations are ADDED.
Hence, equation 1 needs to be multiplied with + 2
and the equation 2 needs to be multiplied with + 5.